Additive Manufacturing and Precipitation Hardening of Low-Alloyed Copper Alloys Containing Chromium and Hafnium - Julia Dölling; Samira Gruber; Felix Kovermann; Lukas Stepien; Elmar Beeh; Elena Lopez; Christoph Leyens; Hans-Günther Wobker; Andreas Zilly (Metals)
Copper alloys with chromium and hafnium offer the possibility of precipitation hardening and combine enhanced strength with high electrical and thermal conductivities. The production process, which starts with raw materials, involves powder production by gas atomization and leads to additive manufacturing by laser powder bed fusion with different parameter sets. The aim is to utilize precipitation reactions afterwards in CuHf0.7Cr0.35 during temperature exposure for further property optimization. This research focuses on the low-alloyed copper alloy with hafnium and chromium, compares this with conventionally manufactured specimens, and relates the alloy to additively manufactured specimens of other benchmark alloys such as CuCr1Zr. Measurements of hardness and electrical conductivity are accompanied by metallographic investigations to understand the behavior of CuHf0.7Cr0.35 manufactured by generative methods. In the as-built condition, melting traces remain visible in the microstructure, and hardness values of 101 HV and an electrical conductivity of 17.5 MS/m are reached. Solution annealing completely recrystallizes the microstructure, and the following quenching holds further alloying elements in supersaturated solid solution, resulting in 73 HV and 16.5 MS/m. Subsequent target-oriented precipitation reactions enable peak values of about 190 HV and 42 MS/m. Future research will assess mechanical and physical properties at elevated temperatures and evaluate possible applications.